(untitled) (Journal of the College of Languages (JCL), 2015)
The Semitic Languages have her its Articulatory That what we attend to discuss In this Research to Represent the Relation Between them and the Light Of Semitics a Comparative Studies where ever It’s Exists The Semitic languages by comparing the words whish most Semitic languages share with each other. We call such Words the Semitic denominator. We have adopted a comparative framework in our Research, which is based on comparing an Arabic word with its Semitic counterpart in Order to identify the forms that control grammatical change in both languages.